Didactic trajectory of learning device development using project-based learning. (February 2020) - Sumarni; Darhim; Fatimah, S
Abstract: The purpose of this study is to describe the role of project-based learning in design a learning trajectory of learning device development to improve mathematical knowledge for teaching of prospective mathematics teachers. The method use is design research with three stages, namely, preliminary design; teaching experiment; retrospective analysis. The subjects of research are prospective mathematics teacher class of 2019 from one university in Kuningan, Indonesia. The use of project-based learning in designing learning trajectory of learning device development plays an essential role as an elicited to improve mathematical knowledge for teaching. This study also describes the design principles and characteristics of the learning trajectory namely didactic trajectory designed by the role of project-based learning syntax.